Meiofauna from Almirante Câmara Canyon and Its Adjacent Open Slope, Southwest Atlantic Ocean - André M. Esteves; Verônica S. Oliveira; Paulo J. P. dos Santos; Tatiana F. Maria; Adriane P. Wandeness (Coasts)
The patterns of meiofaunal distribution in a submarine canyon and adjacent open-slope habitats at Campos Basin, southwest Atlantic, were investigated. A total of eight stations was sampled, four inside the Canyon Almirante Câmara and four on the adjacent open slope. These stations represented four isobaths (400, 700, 1000, 1300 m) and were sampled during two distinct periods (2008, 2009). At each station, three replicates were obtained and sectioned into layers of 0–2, 2–5 and 5–10 cm. Nematoda was the most abundant group in both habitats, comprising more than 85% of the total meiofauna in both sampling periods. The density and assemblage structure of the meiofauna showed high variability between the 400 m isobath and the other three isobaths in the canyon habitat. These results reinforce the roles of habitat heterogeneity and the availability of food sources as key factors strongly influencing the deep-sea meiofauna in the southwest Atlantic Ocean. Phytopigments were significantly correlated with the two major meiofaunal groups (Nematoda and Copepoda), as well as with total meiofaunal density, only in the canyon habitat. On the adjacent open slope, only copepods showed a significant correlation with sediment characteristics (mean grain size and carbonates), suggesting that distinct environmental factors influence the distribution of meiofauna in the two habitats.